Environmental Project Management in the Hospitality Industry in Russia - KOVALTCHUK, Andrey; MILORADOV, Konstantin A.; NIKOLSKAYA, Elena Y.; GUNARE, Marina (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
The authors analyzed the experience of implementing environmental projects by Russian hotels, economic and environmental factors that affect the implementation of projects, and formulated recommendations to encourage the introduction of "green" technologies and environmental standards, considering the regional characteristics of the Russian hospitality market.